Implementation of Desktop Control and Information Retrieval from the Internet Using Augmented Reality (International Journal of Engineering and Computer Science, 2017)
Augmented reality is the technology that brings life to digital world. The technology offers a way using which a user can directly interact with the digital environment. It increases the intuitiveness of any application that would seem unfriendly at first. This technology can be used or attached to certain existing applications to make them more realistic and intuitive. One such application would be interacting with the computer and accessing the information from the internet replacing the conventional mouse and keyboard.